Management of Egg-Bound Syndrome in an Aseel Cross Hen by Digital Milking Method: A Case Report - Banoth, Vennela; Gupta, Chhavi; Akambaram, Sabarinathan; Ramasamy, Rajkumar; Ganesan (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Egg is formed gradually in the different parts of hen’s  reproductive system taking about 24 h (Hasan and  Khaliduzzaman, 2022). In egg bound syndrome a fully or  partially formed egg is lodged in the shell gland (uterus) or  vagina, but cannot be expelled by the bird at a normal rate  (Srinivasan et al., 2014; Muthulakshmi et al., 2015). Chaurasia et al. (2024) reported egg binding is a condition characterized  by the inability of an egg to pass through the cloaca within  the normal timeframe, leading to difficulty in laying leading  a condition known as dystocia in hens. Hosotani et al. (2023)  stated fatigued muscular peristalsis in the oviducts owing  to hypocalcemia, stress, aging, overweight, systemic illness  and abnormalities in the oviductal ciliated epithelium are  linked to internal laying and egg-bound syndrome in hens  along with reduced quality of egg component also alters the  oviductal transportation efficiency. Egg bound syndrome is  commonly noticed in pet birds and broiler breeders (Eitan  and Soller, 2009) resulting in life threatening symptoms and  high mortality in the present report.
Keywords: Hen, Aseel cross, Egg-bound, Digital milking